2002
DOI: 10.4049/jimmunol.168.2.875
|View full text |Cite
|
Sign up to set email alerts
|

Leptin Signaling Deficiency Impairs Humoral and Cellular Immune Responses and Attenuates Experimental Arthritis

Abstract: Leptin is produced almost exclusively by adipocytes and regulates body weight at the hypothalamic level. In addition, recent studies showed that leptin plays an important role in T lymphocyte responses. To examine the role of leptin in Ag-induced arthritis, the development of joint inflammation was assessed in immunized leptin-deficient mice (ob/ob), +/?, and wild-type mice (+/+) following the administration of methylated BSA into the knees. The results showed that ob/ob mice developed less severe arthritis co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
228
1
17

Year Published

2003
2003
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 296 publications
(253 citation statements)
references
References 47 publications
(48 reference statements)
7
228
1
17
Order By: Relevance
“…These findings indicate that the functional defects in DC populations are directly caused by the leptin-signaling deficiency in db/db mice. Abnormalities in the immune system have been reported in db/db mice, which suggests that the immune system might be involved in the pathogenesis of diabetes [29,30]. Recent studies have shown that leptin-deficient ob/ob mice are resistant to induction of experimental autoimmune encephalomyelitis, and leptin blockade inhibits T cell autoreactivity and slows disease progression in SJL/J mice [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…These findings indicate that the functional defects in DC populations are directly caused by the leptin-signaling deficiency in db/db mice. Abnormalities in the immune system have been reported in db/db mice, which suggests that the immune system might be involved in the pathogenesis of diabetes [29,30]. Recent studies have shown that leptin-deficient ob/ob mice are resistant to induction of experimental autoimmune encephalomyelitis, and leptin blockade inhibits T cell autoreactivity and slows disease progression in SJL/J mice [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…69 The milder form of antigen-induced arthritis seen in ob/ob and db/db mice, as compared with their controls, was accompanied by decreased synovial levels of IL-1 and TNF-a and a reduced proliferative response to antigen by lymph node cells in vitro. 57 RA is a chronic systemic inflammatory disease of the synovial tissue.…”
Section: Leptin and Autoimmunity M Vadacca Et Al 207mentioning
confidence: 94%
“…Measurements of serum levels of anti-mBSA antibodies and T cell proliferation assays were performed as described previously (15).…”
Section: Methodsmentioning
confidence: 99%